Assessing Specialized Translation In Academic Contexts: A Case Study - Kim Grego (Altre Modernità, 2012)
This paper discusses translation assessment, first of all by briefly outlining the topic, then by restricting the reflection to specialized translation in didactic contexts and, finally, by discussing how to determine assessment criteria in one specific academic case, the ‘English specialized translation’ course of the ‘Lingue moderne per la comunicazione e la cooperazione internazionale’ Master’s programme of the University of Milan, Italy. Both generic (common to all Master’s programmes in the same ministerial class) and specific (typical of this course) factors were listed, examined and summed up in a preliminary study that may be used as the basis for developing a possible translation assessment model applicable to the case considered.